Sustainable development reporting: trends, drivers, and challenges - O V Efimova (RUDN Journal of Economics, 2012)
This article analyses methodology and best practice of Sustainable Development Reporting (SDR). The research is based on the examination of existing approaches and international experience of SDR. Best practice of international companies was taken into consideration. It is concluded that it is necessary to distinguish the objectives of SDR for both internal and external users. Taking into account the information needs of key users groups the most important performance indicators are offered. The analysis has shown that sustainability reporting in Russia is mainly used by public companies and corporations. To spread the SDR further it is necessary to involve small and medium businesses into the process. The study examines new requirements for Sustainability Development Reporting.